2000
DOI: 10.17221/8330-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural antioxidants on heat-untreated meat products quality

Abstract: The work deals with a study of the effect of natural antioxidants – rosemary extracts in powder and liquid forms, respectively, on the quality of a heat-untreated meat product. Effect of added antioxidants was estimated in samples taken from the meat product mixture, from a ready-made product immediately after smoking, after 28 days – at the expedition of the meat product and then after further 28 days of storing at different ambient temperatures. Marked positive effect of the applied antioxidants was noted es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The mixture of AA ϩ Ros had the most significant effect on reducing the lipid oxidation, followed by Toc ϩ Ros and AA ϩ Toc. These results are in accordance with the results of Korimova et al (1998), who reported that rosemary extract effectively inhibited the formation of PV in meat products. Similar to the current results, Verma and Sahoo, (2000) noted that PV decreased as the α-tocopherol acetate level increased in the meat samples (ground chevron) up to 10 ppm although beyond that, it again increased, resulting in a higher concentration of α-toc because the acetate group blocks the activity of the molecule.…”
Section: Chemical Analysissupporting
confidence: 93%
“…The mixture of AA ϩ Ros had the most significant effect on reducing the lipid oxidation, followed by Toc ϩ Ros and AA ϩ Toc. These results are in accordance with the results of Korimova et al (1998), who reported that rosemary extract effectively inhibited the formation of PV in meat products. Similar to the current results, Verma and Sahoo, (2000) noted that PV decreased as the α-tocopherol acetate level increased in the meat samples (ground chevron) up to 10 ppm although beyond that, it again increased, resulting in a higher concentration of α-toc because the acetate group blocks the activity of the molecule.…”
Section: Chemical Analysissupporting
confidence: 93%
“…These results were in accordance with the results of Korimova et al who reported that rosemary extract effectively inhibited the formation of PV in meat products. 23 During 30 days of storage, the PVs of rice bran tea supplemented with MFP at different proportions were slightly increased from the beginning of the storage period, indicating the initial process of oxidation. However, it is clear from these data that the PV of the rice bran tea without MFP was higher than that of rice bran tea with MFP antioxidants regardless of the storage period.…”
Section: Peroxide Value (Pv)mentioning
confidence: 93%